Public Health Communication By Health Workers During COVID-19: A Study Of Jalandhar District Of Punjab - Sharma, Nidhi; Nahak, Dr. Fakira Mohan (The journal of contemporary issues in business and government, 2021)
Everything can be regained except the human body. Once it is lost, it can not be obtained. It clearly shows the importance of health. So health is an important component for the development of the society. ‘Health for All’ is one of the major objectives of the Sustainable Development Goals (SDGs) for 2030. But in the year 2020 health is adversely effected by COVID-19. As a result major health issues are pushed to back seat and it became secondory for administration, for governments as well as for society too. Punjab is also facing major health issues like drug addiction, cancer, tuberoculosis and other daily pertaining health issues. Most of these issues are ignored because of COVID-19. This pandemic compelled all governments and health workers to focus on COVID management. This sitution not only effecing the masses general health, but also affects psychologically and socially. It has affected the peoples’ behaviour and social dimensions also. The major objectives of this study to know about role of media during COVID-19 and setting the health agenda for masses and secondly trying to set up inter relationship between health and communication. Researcherss have interviewed different health workers to analyse their mind set about health and related issues. Also analysied government running COVID-19 related schemes as secondary data. The study concludes that during COVID-19 health communication by health workers was completely focused on pandemic awarness and precautions, but all other health issues are not on priority. Surprisingly majority of grass root health workers are not aware of SDGs and health related targets. They are using traditional along with digital mediums of communication. In one line it can be concluded that, this year life survival is important rather than health agenda for all.